The Capsule Depolymerase Dpo48 Rescues Galleria mellonella and Mice From Acinetobacter baumannii Systemic Infections - Liu, Yannan; Leung, Sharon Shui Yee; Guo, Yatao; Zhao, Lili; Jiang, Ning; Mi, Liyuan; Li, Puyuan; Wang, Can; Qin, Yanhong; Mi, Zhiqiang; Bai, Changqing; Gao, Zhancheng (Frontiers in Microbiology, 2019)
The emergence of multidrug- and extensively drug-resistant Acinetobacter baumannii has made it difficult to treat and control infections caused by this bacterium. Thus, alternatives to conventional antibiotics for management of severe A. baumannii infections is urgently needed. In our previous study, we found that a capsule depolymerase Dpo48 could strip bacterial capsules, and the noncapsuled A. baumannii were significantly decreased in the presence of serum complement in vitro. Here, we further explored its potential as a therapeutic agent for controlling systemic infections caused by extensively drug-resistant A. baumannii. Prior to mammalian studies, the anti-virulence efficacy of Dpo48 was first tested in a Galleria mellonella infection model. Survival rate of Dpo48-pretreated bacteria or Dpo48 treatment group was significantly increased compared to the infective G. mellonella without treatment. Furthermore, the safety and therapeutic efficacy of Dpo48 to mice were evaluated. The mice treated with Dpo48 displayed normal serum levels of TBIL, AST, ALT, ALP, Cr, BUN and LDH, while no significant histopathology changes were observed in tissues of liver, spleen, lung and kidney. Treatment with Dpo48 could rescue normal and immunocompromised mice from lethal peritoneal sepsis, with the bacterial counts in blood, liver, spleen, lung and kidney significantly reduced by 1.4–3.3 log colony-forming units at 4 h post treatment. Besides, the hemolysis and cytotoxicity assays showed that Dpo48 was non-homolytic to human red blood cells and non-toxic to human lung, liver and kidney cell lines. Overall, the present study demonstrated the promising potential of capsule depolymerases as therapeutic agents to prevent antibiotic-resisitant A. baumannii infections.